Bahasa Prokem pada Peristiwa Tutur Siswa MAN 2 Kota Serang - Lia Andriani; Idawati Idawati; Amaliyah Amaliyah; Odin Rosidien (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This research examines the form of prokem language in speech events used by MAN 2 Serang City students. The aim of this research is to describe the use of prokem language forms in the speech events of MAN 2 Serang City students. This research uses a descriptive research approach as its method. Data collection was carried out through field observations, recording dialogue results, interviews with a list of questions, as well as listening and note-taking methods. The data analysis process in this method uses a descriptive approach. The technique used in this research is a distributional technique. The research results show four processes of morphological formation of prokem language in the speech events of MAN 2 Serang City students, namely abbreviations, acronyms, affixation and reduplication. Apart from that, there are words taken from regional/Javanese languages, taken from English, and the creation of new words with new meanings. In the formation of the phonology of prokem language vocabulary, namely reversal of syllables, replacement of vowels and consonants.